2019
DOI: 10.1101/866780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agonist-selective recruitment of engineered protein probes and of GRK2 by opioid receptors in living cells

Abstract: G protein-coupled receptors (GPCRs) signal through allostery, and it is increasingly clear that chemically distinct agonists can produce different receptor-based effects. It has been proposed that agonists selectively promote receptors to recruit one cellular interacting partner over another, introducing allosteric 'bias' into the signaling system. However, the core underlying hypothesisthat different agonists drive GPCRs to engage different cytoplasmic proteins in living cellsremains untested due to the compl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 51 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…The development of synthetic lipid bilayers, including rHDL particles/nanodisks, has enabled the first characterization of the structure and dynamics of membrane-reconstituted GPCRs by using cryo-EM, solution NMR, DEER, and fluorescence spectroscopy [70,75,89,90,106,120,132,133,200,[207][208][209]. In addition, intramolecular FRET and BRET sensors as well as conformation-specific intracellular biosensors (nanobodies and engineered Ga subunits) have been employed to detect receptor and transducer activation in living cells [210][211][212][213][214]. Future applications of unnatural amino acids to label GPCRs and their effector proteins with small fluorescent probes will be required to enable the characterization of the conformational ensemble and state transitions of receptors and transducers in their cellular context with high spatial and temporal resolution.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…The development of synthetic lipid bilayers, including rHDL particles/nanodisks, has enabled the first characterization of the structure and dynamics of membrane-reconstituted GPCRs by using cryo-EM, solution NMR, DEER, and fluorescence spectroscopy [70,75,89,90,106,120,132,133,200,[207][208][209]. In addition, intramolecular FRET and BRET sensors as well as conformation-specific intracellular biosensors (nanobodies and engineered Ga subunits) have been employed to detect receptor and transducer activation in living cells [210][211][212][213][214]. Future applications of unnatural amino acids to label GPCRs and their effector proteins with small fluorescent probes will be required to enable the characterization of the conformational ensemble and state transitions of receptors and transducers in their cellular context with high spatial and temporal resolution.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In addition to their usefulness as surrogates for heterotrimeric G proteins in structural studies, mini-G proteins are currently used extensively as probes to report GPCR activation in living cells, similar to nanobodies (Wan et al 2018). The mini-Gsi probe has proven to be a robust biosensor for KOR activation (Stoeber et al 2020). Of note, it can bind to various active state Gi-coupled receptors, while Nb33, Nb39 and Nb6 couple selectively to members of the opioid receptor family.…”
Section: Active State Binding Mini-g Protein Mini-gsimentioning
confidence: 99%
“…In addition, desired characteristics of a biosensor include specificity, reversibility, and the ability to report on GPCR signaling without interfering with it. The ability of Nb39, Nb33, Nb6, and mini-Gsi to act as optical biosensors for KOR activation in intact cells with high specificity, sensitivity, and high temporal and spatial resolution has recently been demonstrated (Che et al 2020;Stoeber et al 2020). As a straightforward approach, the different nanobodies and mini-G proteins have been fused with fluorescent proteins and ligand-dependent recruitment to fluorescently-labelled KOR has been determined by fluorescence microscopy.…”
Section: Biosensors Robustly and Rapidly Report On Kor Activation And Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[17][18][19][20][21][22][23] Previous reports from our group reported that mitragynine (possessing an indole core), its oxidation product 7OH (possessing an indolenine core), and mitragynine pseudoindoxyl (MP, a skeletal rearrangement product of 7OH with a spiro-pseudoindoxyl core) (Figure 1A), are all opioid antinociceptive agents 18,19 and Gprotein biased MOR agonists. 17,18,20,22 We also reported oxidative metabolism of mitragynine to 7OH mitragynine using a CYP3A-mediated pathway following oral administration of mitragynine in mice. 19 Metabolism of mitragynine to 7OH in vitro 24 and in dogs 25 has been reported by other groups too.…”
Section: Introductionmentioning
confidence: 99%